2019
DOI: 10.1111/jfbc.12933
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antihyperlipidemic effects of Ajwa date (Phoenix dactyliferaL.) extracts in rats fed a cholesterol‐rich diet

Abstract: This study investigated the chemical composition, in vivo antioxidant, and antihyperlipidemic potential of Ajwa date polyphenol extract (DPE). Chemical analysis revealed that the Ajwa dates contain substantial amounts of carbohydrates, energy, potassium, iron, polyphenols, and flavonoids. In vivo studies showed that feeding rats with cholesterol‐rich diets significantly (p ≤ 0.05) increased their body and liver weights, total cholesterol (TC), low‐density lipoprotein cholesterol (LDL‐C), very‐low‐density lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 31 publications
(65 reference statements)
1
25
0
2
Order By: Relevance
“…Besides, date seeds are used as animal feed or caffeine-free coffee replacements in some areas. The Ajwa date seed oil includes sterol, phytochemistry, oleic, palmitic and fatty acids and their derivatives; these have antibacterial, antioxidant, anticancer and antilipidemic effects [72,73]. The present work reported that Ajwa date seed oil (AWSO) contains hexadecanamide, 5-hydroxymethylfurfura, 9-octadecenamide, (Z)-, oleic acid, cis-11-eicosenamide, dodecanoic acid and palmitic acid.…”
Section: Discussionmentioning
confidence: 88%
“…Besides, date seeds are used as animal feed or caffeine-free coffee replacements in some areas. The Ajwa date seed oil includes sterol, phytochemistry, oleic, palmitic and fatty acids and their derivatives; these have antibacterial, antioxidant, anticancer and antilipidemic effects [72,73]. The present work reported that Ajwa date seed oil (AWSO) contains hexadecanamide, 5-hydroxymethylfurfura, 9-octadecenamide, (Z)-, oleic acid, cis-11-eicosenamide, dodecanoic acid and palmitic acid.…”
Section: Discussionmentioning
confidence: 88%
“…Ghiaba et al [29] studied five varieties of Algerian date palm fruit by cyclic voltammetric technique and reported that IC 50 against the superoxide anion radical was ranged from 33.17 -85.23 mg/L. Another study conducted by Algarni et al [11] reported that oral administration of Ajwa date extract showed significant increase of superoxide dismutase (SOD) enzyme in hypercholesterolemic rats, however, the increase of SOD activity is in agreement with our finding that DPL extracts possess a good scavenging activity against superoxide anion.…”
Section: Dpl Scavenging Activity Against Superoxide Anion Radicalmentioning
confidence: 99%
“…Ajwa date polyphenol extract is reported to be a good source of phytochemical and micronutrients, thereafter, administration of Ajwa date polyphenol extract to hypercholesterolemic rats improved serum lipid profile and the antioxidant status in liver and plasma tissues [11]. Saryono et al [12] reported that the levels of total cholesterol and LDL were significantly decreased in rats induced with high cholesterol diet, after their diet has been supplemented with PDS extract.…”
Section: Introductionmentioning
confidence: 99%
“…I 2 for heterogeneity=79%, P <0.00001 and postprandial plasma glucose (PPPG), odd ratio -28.19, 95% CI= -60.66-4.29, P =<0.0001. I 2 for heterogeneity=92%, P =0.09) was observed. While the effect on HbA1 c was neutral, odd ratio, -.20, 95% CI=-.46 -.06, P=0.13.…”
mentioning
confidence: 99%
“…While the effect on HbA1 c was neutral, odd ratio, -.20, 95% CI=-.46 -.06, P=0.13. I 2 for heterogeneity=0. %, P=0.55.…”
mentioning
confidence: 99%